1995
DOI: 10.1002/mus.880181009
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration across preserved peripheral nerve grafts

Abstract: The potential to store nerve grafts for a prolonged period of time was assessed in a rat sciatic nerve model. Three-centimeter syngeneic nerve grafts were stored in Belzer/University of Wisconsin cold storage solution at different temperatures (5 degrees C, 22 degrees C, or 37 degrees C) for varying time periods (6 h, 24 h, or 3 weeks) prior to transplantation. Functional assessment using serial walking track analyses revealed no difference between storage times and temperatures. At 14 months postengraftment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 25 publications
1
46
1
3
Order By: Relevance
“…Recently, we assessed short-term graft storage in an autograft model and found that regeneration and function across autografts stored at 5°C for 21 days was equivalent to fresh autografts. 16,17 Nerve allograft pretreatment by repeated cycles of deep freezing and thawing to render grafts acellular was first described by Sanders in 1954 61 and is of current interest. 12,18,25,28,33,54,55,65,67 Freeze-thawing was found to prevent effectively the lymphocyte infiltrate seen in fresh allografts and allow regeneration similar to autografts.…”
mentioning
confidence: 99%
“…Recently, we assessed short-term graft storage in an autograft model and found that regeneration and function across autografts stored at 5°C for 21 days was equivalent to fresh autografts. 16,17 Nerve allograft pretreatment by repeated cycles of deep freezing and thawing to render grafts acellular was first described by Sanders in 1954 61 and is of current interest. 12,18,25,28,33,54,55,65,67 Freeze-thawing was found to prevent effectively the lymphocyte infiltrate seen in fresh allografts and allow regeneration similar to autografts.…”
mentioning
confidence: 99%
“…Previous studies have tried using UWS for nerve graft preservation in peripheral nerve allotransplantation (Levi et al, 1994;Evans et al, 1995). However, it has been found that while short storage intervals of less than one week in UWS alone resulted in peripheral nerve segments containing functioning SCs, the long-term preservation of peripheral nerve segments for more than three weeks caused a substantial loss of SCs (Levi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Most pretreatment methods, such as chemical treatment, irradiation, freezing, lyophilization, and freezethawing could effectively reduce nerve graft antigenicity; however, nerve regeneration remains inferior to autografts. One problem has been acellularizing the graft (Song, Yang, Russell, 2009), and although short nerve deficits (less than 3 cm) can be bridged by acellular grafts, longer deficits may be more dependent upon the presence of donor-derived viable SCs (Hems, Glasby, 1992;Evans et al, 1995;Strauch et al, 1996;Song, Yang, Russell, 2009), because viable SCs are essential for successful axonal regeneration through longer deficits (Hall, 1986;Feneley, Fawcett, Keynes, 1991;Bunge, 1993). Furthermore, Blais, Grenier, Berthod and Sun et al found that tissueengineered skin or acellular nerve allografts seeded with SCs could improve nerve regeneration (Blais, Grenier, Berthod, 2009;Sun et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although natural materials are ideal, there are some inherent difficulties and these include undesirable immune responses, the potential use of immunosuppressive drugs, and batch to batch variation (Hudson et al, 1999). In an attempt to use natural material, nerve grafts have been stored for prolonged periods of time (Evans et al, 1995). However, it appear as the degeneration interval increased, the regenerative supporting ability of the stored nerve is compromised (Gulati, 1996).…”
Section: Scaffoldmentioning
confidence: 99%